Tuberculosis in diabetic patients: a clinical perspective - Nissapatorn, V.; Kuppusamy, I.; Jamaiah, I.; Fong, Mun Yik; Rohela, M.; Anuar, A.K. (2005)
This retrospective and descriptive study was a report on the clinical situation of tuberculosis in diabetic patients, with 1,651 patients recruited. The mean age of TBDM patients was significantly higher than that of non-diabetic patients (p<0.05). Moreover, TBDM patients had a higher ratio of male to female than the other group. The significant proportion of TB appeared to increase steadily with age in diabetic patients compared to non-diabetic ones (p<0.05). However, they showed similarities in terms of sex, race, marital status, present address, and occupation. A higher percentage of pulmonary tuberculosis (91.4) was shown in the TBDM group. We found that both groups had no differences in the radiological findings, with opacity or cavity of the upper lobe involvement being 89 and 91 in TBDM and non-diabetic groups, respectively. TBDM patients were shown to have more treatment success (33.3), particularly the pulmonary type of tuberculosis in the longer duration (â¥ 9 months). Further findings demonstrated that a lower proportion of the TBDM group defaulted in their treatment (19.8) and experienced resistance to anti-tubercular therapy (1.4) compared to non-diabetics.